Cauliflower ear among Finnish high-level male wrestlers and judoka. - Manninen, I.-K.; Blomgren, K.; Elokiuru, R.; Lehto, M.; Mäkinen, L. K.; Klockars, T. (International Journal of Wrestling Science, 2019)
AIM OF THE STUDY: To study the prevalence, concerns, and treatment practices related to cauliflower ear among Finnish wrestlers and judokas. BACKGROUND "« Cauliflower ear is an acquired deformity of the auricle caused by trauma "« Prevalence among wrestlers 39% - 44% "« Haematoma between perichondrium and auricular cartilage results in cartilage necrosis followed by fibroneocartilage formation (Schuller Arch Otolaryngol Head Neck Surg 1989; Kordi RJ Sports Sci Med. 2007) Cauliflower ear may cause: "« aesthetic discomfort "« ear canal obstruction may cause cerumen accumulation "« external ear infections and even hearing loss. Haematomas should be evacuated promptly to avoid formation of cauliflower ear. Treatment options are aspiration or incision with post-drainage interventions such as suturing, dressings or splints to prevent the reaccumulation of the haematoma. Protective headgear is suggested to reduce the occurrence of cauliflower ear.